Nutritional survey among under five children at Tamyia district in Fayoum, Egypt - Elsary, Asmaa Younis; Abd El-moktader, Ahmed Mahmoud; Elgameel, Alkassem; Mohammed, Wael Sayed; Masoud, Mohamed; Abd El-Haleem, Naglaa Gamal (International Journal Of Community Medicine And Public Health, 2017)
Background: Malnutrition is involved in half of the deaths of under-five children as in many developing countries. In Egypt, malnutrition remains an important issue as 5.5% of under-five children are underweight, 8.4% are wasted and 21.4% are stunted. The present study was carried out to assess the prevalence and risk factors of malnutrition among sick under five children seeking medical advice at Tamiya District health care facilities in Fayoum. Methods: This cross-sectional descriptive study included 400 under five children at Tamiya district in Fayoum. It was carried out over a period of 5 months from June to October 2014. All patients were subjected to the following: History taking, anthropometric measurements including weight and length/height. Results: Our study shows that 23.2%, 18.5% and 19.3% of children were underweight, stunted and wasted, respectively. Stunting was more common in females than males. Also, our results reveal that risk factors of malnutrition were 70.6% parasitic infestation and 15.7% for gastroenteritis with statistically significant high prevalence of positive parasitic, helminthic infestation, and gastroenteritis with p-value <0.05 among wasted, stunted, and underweighted children. Conclusions: Prevalence of malnutrition was high among under five sick children. These findings indicate the need for implementing hospital and community-based intervention nutritional program.